R47H TREM2 variant increases risk of typical early‐onset Alzheimer's disease but not of prion or frontotemporal dementia. Issue 6 (23rd August 2014) - Slattery, Catherine F.; Beck, Jonathan A.; Harper, Lorna; Adamson, Gary; Abdi, Zeinab; Uphill, James; Campbell, Tracy; Druyeh, Ron; Mahoney, Colin J.; Rohrer, Jonathan D.; Kenny, Janna; Lowe, Jessica; et al.
Abstract: Background: Rare TREM2 variants are significant risk factors for Alzheimer's disease (AD). Methods: We used next generation sequencing of the whole gene (n = 700), exon 2 Sanger sequencing (n = 2634), p.R47H genotyping (n = 3518), and genome wide association study imputation (n = 13, 048) to determine whether TREM2 variants are risk factors or phenotypic modifiers in patients with AD (n = 1002), frontotemporal dementia (n = 358), sporadic (n = 2500), and variant (n = 115) Creutzfeldt‐Jakob disease (CJD). Results: We confirm only p.R47H as a risk factor for AD (odds ratio or OR = 2.19; 95% confidence interval or CI = 1.04‐4.51; P  = .03). p.R47H does not significantly alter risk for frontotemporal dementia (OR = 0.81), variant or sporadic CJD (OR = 1.06 95%CI = 0.66‐1.69) in our cohorts. Individuals with p.R47H associated AD (n = 12) had significantly earlier symptom onset than individuals with no TREM2 variants (n = 551) (55.2 years vs. 61.7 years, P  = .02). We note that heterozygous p.R47H AD is memory led and otherwise indistinguishable from "typical" sporadic AD. Conclusion: We find p.R47H is a risk factor for AD, but not frontotemporal dementia or prion disease.